2016
DOI: 10.3329/fmcj.v11i1.30868
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Obstetric Hysterectomy: A Review of 40 cases in Faridpur Medical College Hospital

Abstract: Abstract:Emergency obstetric hysterectomy is removal of part or whole of the uterus done to save the life of a mother in complications in the intra partum or post-partum period. This study was done to assess the cases of emergency obstetric hysterectomy (EOH) in view to find out the indications, the patient profile, the risk factors, the morbidity and mortality associated with the procedure. It was a retrospective analysis of 40 cases of obstetric hysterectomy performed in Faridpur Medical College Hospital (FM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Most frequent complications noted in our study were hypovolemic shock, visceral injury, coagulopathy and relaparotomy (8.32% each). These findings are like those reported by Chauhan et al14 .Mahbuba et al observed shock in 12.5% of the patients of EOH group 15. They found it in post-operative period.…”
supporting
confidence: 90%
“…Most frequent complications noted in our study were hypovolemic shock, visceral injury, coagulopathy and relaparotomy (8.32% each). These findings are like those reported by Chauhan et al14 .Mahbuba et al observed shock in 12.5% of the patients of EOH group 15. They found it in post-operative period.…”
supporting
confidence: 90%
“…Emergency peripartum hysterectomy (EPH) is a life‐saving obstetrical procedure reserved for postpartum hemorrhage that is not amenable to medical treatment and conservative surgery and also for abnormal placentation which is beyond the conservative surgical methods. It is defined as removal of part or whole of the uterus during cesarean section, following cesarean section, immediately after vaginal delivery, or during the puerperium in an attempt to avoid maternal death from grave complications related to childbirth in the intrapartum or postpartum period within 42 days of birth 1–3 . It is associated with significant morbidity and mortality with significant psychological trauma to the family as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as removal of part or whole of the uterus during cesarean section, following cesarean section, immediately after vaginal delivery, or during the puerperium in an attempt to avoid maternal death from grave complications related to childbirth in the intrapartum or postpartum period within 42 days of birth. [1][2][3] It is associated with significant morbidity and mortality with significant psychological trauma to the family as a whole. It is listed by WHO as an identification criterion for maternal near-miss.…”
mentioning
confidence: 99%